Stability and Performance Evaluation of Advanced Bread Wheat (Triticum aestivum L.) Genotypes in Optimum Areas of Ethiopia - Delesa, Abebe; Alemu, Gadisa; Geleta, Negash; Dabi, Alemu; Zegeye, Habtemariyam; Solomon, Tafesse; Duga, Rut; Asnake, Dawit; Tadesse, Zerihun; Asefa, Bayisa; et al. (International Journal of Bio-resource and Stress Management, 2022)
Multi-environment trials were carried out at 11 locations in different wheat growing zones of Ethiopia during 2017–18 and 2018–19 to identify high yielding, stable, biotic and abiotic stresses resistant varieties with improved quality traits for commercial release. Twenty-eight advanced bread wheat genotypes have been evaluated against two released bread wheat varieties. The experiment was laid out using alpha lattice design with three replications. Nine stability models were employed in order to assess stability and performance of 28 advanced bread wheat genotypes across 18 diverse environments. Combined analysis of variance for grain yield has revealed that the environments, the genotypes and GEI effects were significantly different (p<0.001). Environments, GEI and Genotypic effects accounted for 71.99%, 22.97% and 5.03% of the total grain yield variation, respectively. Significant GEI showed variable performance of genotypes across environments. Eight advanced bread wheat genotypes namely ETBW8595, ETBW8668, ETBW8751, ETBW8991, ETBW8996, ETBW9547, ETBW9553 and ETBW9554 produced grain yield of more than 5.0 t ha-1, indicating their superior yielding potential. ETBW8595, ETBW8668, ETBW8751, ETBW8991 and ETBW9554 were found the most stable bread wheat genotypes as confirmed by five to eight stability models. ETBW8751, ETBW8991 and ETBW9554 were highest yielding, stable, adaptable, resistant and moderately resistant to prevailing stem and yellow rust diseases. Thus, these three genotypes were the most promising advanced bread wheat genotypes to be verified and released in Ethiopia. These promising bread wheat genotypes can be included in multipurpose bread wheat crossing blocks in order to correct shortcomings of commercial varieties.